2021
DOI: 10.3390/polym13172848
|View full text |Cite
|
Sign up to set email alerts
|

New Principles of Polymer Composite Preparation. MQ Copolymers as an Active Molecular Filler for Polydimethylsiloxane Rubbers

Abstract: Colorless transparent vulcanizates of silicone elastomers were prepared by mixing the components in a common solvent followed by solvent removal. We studied the correlation between the mechanical behavior of polydimethylsiloxane (PDMS)-rubber compositions prepared using MQ (mono-(M) and tetra-(Q) functional siloxane) copolymers with different ratios of M and Q parts as a molecular filler. The composition and molecular structure of the original rubber, MQ copolymers, and carboxyl-containing PDMS oligomers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Such observations supported in many aspects our own studies which have demonstrated [ 43 ] that MQ -resins are also very effective as an active filler, significantly enhancing the mechanical properties of vulcanizates, not inferior in efficiency to aerosils, but without requiring the heterophase mixing of ingredients. Of course, such an influence of the molecular filler was expected and even planned.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Such observations supported in many aspects our own studies which have demonstrated [ 43 ] that MQ -resins are also very effective as an active filler, significantly enhancing the mechanical properties of vulcanizates, not inferior in efficiency to aerosils, but without requiring the heterophase mixing of ingredients. Of course, such an influence of the molecular filler was expected and even planned.…”
Section: Introductionsupporting
confidence: 81%
“…The content of amino groups determined by titration was 0.04 wt.%. Detailed synthesis for the used components was described elsewhere [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hyperbranched polymers are universal macromolecular objects that are irregular analogues of dendrimers, combining a number of advantages of the latter with the ease of obtaining of classical polymers. Hyperbranched polymers have now found a wide range of applications, due to the presence of a number of unique physical and chemical properties. , In terms of view of siloxane systems, their easy transformation into nanogels has breathed new life into the concept of obtaining molecular composites. , …”
Section: Resultsmentioning
confidence: 99%
“…51,52 In terms of view of siloxane systems, their easy transformation into nanogels has breathed new life into the concept of obtaining molecular composites. 53,54 One of the methods for obtaining hyperbranched polymers is based on the use of Rebrov's salt 55 − compounds with the general formula R n (OR′) 3−n SiONa, allowing us to obtain diverse siloxane structures, from individual compounds to gels of complex structures. 25,56−59 To demonstrate the versatility of our approach to the functionalization of polysiloxane structures, we used hyperbranched silsesquioxanes of various structures and molecular weights in our work (1-10−1-12).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The development of modern technologies requires more careful control over the properties of the resulting products. One way of realizing this is the use of narrowly dispersed oligomers and polymers. Such compounds allow for tuning the properties of the products by varying the molar mass in a controlled manner.…”
Section: Introductionmentioning
confidence: 99%